Growth and diversification of uses in fishing ports. The role of the Common Fisheries Policy in Galician ports in the 21st century - Felicidades-García, Jesús; Piñeiro-Antelo, María Ángeles; Piñeira-Mantiñán, María José (Revista de Estudios Andaluces, 2023)
Since the end of the 20th century, despite the crisis in the fishing sector in Spain, there has been a significant growth in fishing ports. This is partly due to the fact that the requalification of ports has been an objective of the Common Fisheries Policy (CFP) since the mid-1990s. The aim of the paper is to analyse the impact of this policy, as well as to observe the integration between port and city linked to social demand which makes it possible for fishing uses to coexist with other recreational, sporting or commercial uses. The case study focuses on the ports of Muros and Ribeira (Galicia), based on a combined quantitative and qualitative analysis, using statistical and cartographic sources (SIOSE programme and photointerpretation) and fieldwork. The results show a significant growth and diversification of port uses, at the same time as a reduction in the number and power of the fishing fleet (SGP, 2021). The authors highlight the absence of a master plan to guide investments at regional level, and, in general, of sectoral and urban planning instruments to harmonise these processes.